Clinical utility of low‑frequency piezoelectric thromboelastography for global hemostasis assessment and prediction of thrombo‑hemorrhagic complications - Tarabrin, O.; Sukhonos, R.; Kirpichnikova, K.; Buhayenko, Ye.; Hladkykh, I.; Suslov, O. (Journal of Education, Health and Sport, 2025)
Background. Venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), remains a major cause of preventable in‑hospital morbidity and mortality worldwide. Conventional coagulation tests (prothrombin time, activated partial thromboplastin time, fibrinogen, D‑dimer) provide only a static snapshot of hemostasis and do not adequately reflect the global hemostatic potential (HP) or hypercoagulable states, particularly in high‑risk surgical patients. There is growing interest in “global” viscoelastic methods such as thromboelastography (TEG) and low‑frequency piezoelectric thromboelastography (LPTEG) for dynamic, point‑of‑care assessment of the Blood Aggregation Regulation System (RAS) and hemostatic potential. Objective. To describe the methodological principles and analytical parameters of low‑frequency piezoelectric thromboelastography and to evaluate its potential for dynamic assessment of hemostasis and prediction of thrombo‑hemorrhagic risk, including in combination with the functional stress test “double local hypoxia of the upper limb” (DLHUL). Methods. LPTEG records changes in the viscoelastic properties of whole blood during hemocoagulation, from a liquid to a solid‑elastic state, yielding an integrated curve (A0–A6, t1–t5). Primary analytical parameters include contact coagulation intensity (CCI), intensity of coagulation drive (ICD), constant of thrombin activity (CTA), intensity of clot polymerization (IPC), maximum amplitude (MA), intensity of total coagulation (ITC), intensity of clot retraction and lysis (IRCL), and coefficient of total anticoagulation activity (CTAA). Pre‑analytical conditions were standardized (venous blood sampling with a 1.0‑mL silicone syringe without tourniquet, time from sampling to cuvette ≤ 20 s). The study included 40 healthy volunteers (Group 1) and 120 surgical patients with risk factors for thrombosis (Group 2). All participants underwent a functional DLHUL test (two brief episodes of arterial and venous occlusion of the upper limb separated by a 20–25‑minute interval), with LPTEG recorded before and after the test. Results. In Group 1 (without clinical predictors of thrombotic risk), two distinct patterns of hemostatic response to DLHUL were identified: a compensated type (decrease in platelet‑vascular indices, enhanced fibrinolysis, shift of HP toward hypocoagulation) and a subcompensated type (increase in CCI, shortening of clotting time, shift of HP toward hypercoagulation). These patterns occurred with similar frequency (20/40 each. In Group 2 (patients with thrombotic risk factors), baseline LPTEG already showed increased platelet aggregation, activation of the coagulation link (elevated ICD and MA), and reduced fibrinolytic activity (decreased IRCL). After DLHUL, CCI increased by 21.07%, A0 by 5.87%, ICD by 8.51%, and MA by 8.17%, while IRCL decreased by 23.67%, indicating further progression toward hypercoagulation and suppression of fibrinolysis. Most patients in Group 2 demonstrated decompensated (n = 98) or exhausted (n = 22) hemostatic responses, with limited adaptive reserve of the anticoagulant and fibrinolytic systems. Conclusions. LPTEG provides a comprehensive, real‑time assessment of hemostatic potential that surpasses conventional laboratory tests by simultaneously characterizing platelet‑vascular, coagulation, fibrinolytic, and anticoagulant components. The combination of LPTEG with the DLHUL functional test enables identification of compensated, subcompensated, decompensated, and exhausted hemostatic response types, facilitates stratification of perioperative thrombo‑hemorrhagic risk, and supports individualized thromboprophylaxis and anticoagulant therapy. Low‑frequency piezoelectric thromboelastography is a promising tool for dynamic hemostasis monitoring in surgical and critically ill patients.